Death in the stars - Brody, Frances (Brody, Frances. Kate Shackleton mystery., 2018)
"France Brody captures the atmosphere and language of 1920s England while delivering a captivating plot in the ninth book of this traditional cozy mystery series featuring private investigator Kate Shackleton. Yorkshire, 1927. Eclipse fever grips the nation, and when beloved theatre star Selina Fellini approaches trusted sleuth Kate Shackleton to accompany her to a viewing party on thegrounds of Giggleswick School Chapel, Kate suspects an ulterior motive. During the eclipse, Selina's friend and co-star Billy Moffatt disappears and is later found dead in the chapel grounds. Kate can't help but dig deeper and soon learns that two other members of the theatre troupe died in similarly mysterious circumstances in the past year. With the help of Jim Sykes and Mrs Sugden, Kate sets about investigating the deaths -and whether there is a murderer in the company. When Selina's elusive husband Jarrod- who was injured in the war and is subject to violent mood swings--comes back on the scene, Kate beginsto imagine something far deadlier at play, and wonders just who will be next topay the ultimate price for fame"--